Foreign direct investment and trade: Between complementarity and substitution. Evidence from European Union countries - Marian Cătălin Voica; Mirela Panait; Eglantina Hysa; Arjona Cela; Otilia Manta (Journal of Risk and Financial Management, 2021)
This aim of this work is to study the relationship between foreign direct investment (FDI) and trade. FDI is a driving force for economic growth for host countries. The positive effects of FDI are seen in many aspects of the economy. However, the implications of FDI on foreign trade are questionable. Therefore, this study uses a Granger causality technique to test whether the relationship between FDI and foreign trade is complementary or substitutive. The findings of this study indicate that this relationship appears to be complementary, and FDI investment does cause an increase in trade flow in the countries that are taken into consideration. This research aims to make a comparison between the relations of FDI flows of three groups of countries from the European Union (EU)-Romania and Bulgaria, the Visegrád Group and the Euro area-for the period of 2005 to 2019. However, the results indicate that this link between the variables is not yet found for the three group of countries, and further research is required in this aspect. This leads to the conclusion that the FDI impact on foreign trade of the host country depends on the type of investment and absorptive capacity of the receiver, the economic development of host and home countries, and not every type of FDI leads to more trade.
Keywords: 330; foreign direct investment; trade; complementarity; substitution; EU countries; economic growth